Collagens of Poriferan Origin - Hermann Ehrlich; Marcin Wysokowski; Sonia Żółtowska-Aksamitowska; Iaroslav Petrenko; Teofil Jesionowski (Marine Drugs, 2018)
The biosynthesis, structural diversity, and functionality of collagens of sponge origin are still paradigms and causes of scientific controversy. This review has the ambitious goal of providing thorough and comprehensive coverage of poriferan collagens as a multifaceted topic with intriguing hypotheses and numerous challenging open questions. The structural diversity, chemistry, and biochemistry of collagens in sponges are analyzed and discussed here. Special attention is paid to spongins, collagen IV-related proteins, fibrillar collagens from demosponges, and collagens from glass sponge skeletal structures. The review also focuses on prospects and trends in applications of sponge collagens for technology, materials science and biomedicine.